The role of endothelial dysfunction in the development of clinical manifestations of climacteric syndrome in premenopausal women - О. В. Занько; Л. В. Болгова; Н. В. Коваленко; Т. Ф. Татарчук; Н. В. Яроцька (Publishing House TRILIST, 2017)
The aim of the study was to determine the state of vascular microcirculation in women with clinical manifestations of climacteric syndrome (CS) and to study the efficacy of using oral forms of L-arginine in its treatment. Materials and methods. 62 patients aged 40-50 years were examined: 30 patients with clinical manifestations of CS and 32 patients without signs of CS. The severity of CS was assessed using the menopausal rating scale (MRS). The study of hormonal homeostasis consisted in determining the levels of estradiol, FSH, LH, TSH and prolactin. The evaluation of the state of the vessels of the microcirculatory bed was carried out with the help of a test with «reactive hyperemia» and laser doppler fluorometry (LDF) with occlusion test. All patients with signs of endothelial dysfunction were prescribed an oral form of L-arginine -Valargin in a dose of 1 tablet per day during 1 month, after which a repeated examination of the state of the vascular endothelium was carried out. Results. When comparing the hormonal status, a decrease in the average level of estradiol and an increase in the average FSH indices in the main group were found in comparison with the control group. Based on the results of the test with «reactive hyperemia», a significantly higher level of pathological response to occlusion was revealed in comparison with the control group. In addition, a significant direct correlation was found between the level of estrogens and the index reflecting the activity of endotheliocytes. 1 month after Valargin application the degree of CS on the MRS scale decreased from 14.7 ± 1.5 to 8.6 ± 1.3 points. Conclusion. In patients with clinical manifestations of CS endothelial dysfunction is more reliably detected. This requires additional testing and the use of preventive measures aimed at preventing cardiovascular pathology. The efficacy of oral forms of L-arginine in adequately high doses, in particular Valargin, in the treatment of endothelial dysfunction and the positive effect of this therapy in patients with CS is proved.